Розрахунок робочих параметрів високовольтної системи відбору потужності фотоелектричної станції - Зайцев, Р.В.; Кириченко, М.В.; Холод, А.В.; Прокопенко, Д.С.; Хрипунов, Г.С. (Електротехніка і електромеханіка, 2016)
Проведено аналіз роботи системи відбору потужності фотоелектричної станції з використанням підвищувального
перетворювача. Показано, що коефіцієнт корисної дії такої системи в широкому діапазоні освітленості фотоелектричного модуля знаходиться на рівні 0,92, тоді як ефективність класичних систем відбору потужності не перевищує
0,70. Розроблено принципова електрична схема регульованого мостового резонансного підвищуючого перетворювача з
цифровим керуванням, що забезпечує надійність роботи, швидке і точне знаходження точки максимальної потужності і ефективність перетворення до 0,96 Проведен анализ работы системы отбора мощности фотоэлектрической станции с использованием повышающего
преобразователя. Показано, что коэффициент полезного действия такой системы в широком диапазоне освещенности фотоэлектрического модуля находится на уровне 0,92, тогда как эффективность классических систем отбора
мощности не превышает 0,70. Разработана принципиальная электрическая схема регулируемого мостового резонансного повышающего преобразователя с цифровым управлением, обеспечивающая надежность работы, быстрое и точное нахождение точки максимальной мощности и эффективность преобразования до 0,96. Purpose. To ensure maximum production of electric power by
photovoltaic vacilities, in addition to using highly efficient
photovoltaic modules equipped with solar radiation concentrators must use a highly effective power take-off system. This paper is inscribed to solving the problem of a highly efficient and
economic power take-off system development. Methodology. To
solving the problem, we implemented three stages. On the first
stage examines the dependence of electrical power from the
intensity of the incident solar radiation. Based on this, the second stage is calculated the DC-DC converter resonant circuit
and its working parameters, and developed circuit diagram of
DC-DC converter. On the third stage, we carry out an analysis
of power take-off system with step up DC-DC converter working. Results. In this paper, we carry out the analysis of working
efficiency for photovoltaic facility power take-off system with
step-up boost converter. The result of such analysis show that
the efficiency of such system in a wide range of photovoltaic
energy module illumination power is at 0.92, whereas the efficiency of classic power take-off systems does not exceed 0.70.
Achieved results allow designing a circuit scheme of a controlled bridge resonant step-up converter with digital control.
Proposed scheme will ensure reliable operation, fast and accurate location point of maximum power and conversion efficiency
up to 0.96. Originality. Novelty of proposed power take-off system solution constitute in implementation of circuit with DC-DC
converters, which as it shown by results of carrying out modeling is the most effective. Practical value. Practical implementation of proposed power take-off system design will allow reducing losses in connective wires and increasing the efficiency of
such a system up to 92.5% in wide range of photovoltaic energy
modules illumination